Personality and subjective assessment of body weight of tennis players - Piepiora, Paweł; Superson, Magdalena; Migasiewicz, Juliusz (Journal of Education, Health and Sport, 2019)
Aim. The aim of the study was to check the relationship between individual personality traits and the subjective assessment of the weight of tennis players. Material and methods. Personality assessment was performed using the NEO-FFI questionnaire, subjective assessment of body weight was made using a questionnaire. 15 tennis players aged 19.13 years ± 2.97 participated in the tests. Results. The research showed that all tennis players are characterized by low levels of neuroticism, average level of extraversion, average level of openness to experience, low level of agreeableness and high level of conscientiousness. The study showed the lack of connection between the level of neuroticism, extraversion, openness to experience, agreeableness and conscientiousness and the subjective assessment of the weight of tennis players. Conclusions. Tennis players are a very uniform group in terms of personality, which may indicate the specificity of the discipline, which in a specific way affects the formation of personality. The lack of connection between personality and body weight may result from a small sample of the tested female players.